Salmeterol plus fluticasone propionate versus fluticasone propionate plus montelukast: a randomised controlled trial investigating the effects on airway inflammation in asthma. - Pavord, I; Woodcock, A; Parker, D; Rice, L (2007)
BACKGROUND: Few studies have compared treatment strategies in patients with asthma poorly controlled on low dose inhaled corticosteroids, and little is known about the effects of different treatments on airway inflammation. In this double-blind, placebo-controlled, parallel group study, we compared the effects of salmeterol plus fluticasone propionate (FP) (Seretide; SFC) and FP plus montelukast (FP/M) on sputum inflammatory markers, airway responsiveness, lung function, and symptoms in adult asthmatics. METHODS: Sixty-six subjects were randomised to SFC or FP/M for 12 weeks. The primary outcome was changes in neutrophil, eosinophil, macrophage, lymphocyte, and epithelial cell levels in induced sputum. Additional outcomes included the change in other sputum markers of airway inflammation, airway responsiveness, symptom control, and lung function. RESULTS: Both treatments had no significant effect on induced sputum inflammatory cells, although there was a trend for a reduction in sputum eosinophils. Both treatments significantly improved airway responsiveness, whereas SFC generally led to greater improvements in symptom control and lung function than FP/M. FP/M led to significantly greater reductions in sputum cysteinyl leukotrienes than SFC (treatment ratio 1.80; 95% CI 1.09, 2.94). CONCLUSION: Both treatments led to similar control of eosinophilic airway inflammation, although PEF and symptom control were better with SFC. STUDY NUMBER: SAM40030 (SOLTA).